2017
DOI: 10.21746/aps.2017.6.11.14
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic potential of essential oil of Melaleuca leucadendra against some agricultural weeds

Abstract: The work was undertaken to investigate the phytotoxic potential of essential oil from Melaleuca leucadendra against three weed species, viz., Echinochloa crus-galli, Cyperus rotundus and Leptochloa chinensis. It was observed that volatile oil (0.25-1.5 mg ml-1) of Melaleuca retarded the germination and growth of all the test weeds in a dose-response bioassay conducted under laboratory conditions. Generally, both root and shoot length showed an inhibitory effect in a concentration dependent manner and the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Ahuja et al, (2015) showed that the herbicidal potential of clove (Syzygium aromaticum) against four selected weeds (Ageratum conyzoides, Cassia occidentalis, Bidens pilosa and Commelina benghalensis). Goyal (2017) abtracted that the allelopathic impact of essential oil from Melaleuca leucadendra against three selected weeds (Echinochloa crus-galli, Cyperus rotundus and Leptochloa chinensis). Ayeni (2017) stated that the allelopathic potential of leaves from two selected plants (Senna siamea and Pinus carribaea) inhibited of the seed germination and seedling growth in Euphorbia heterophylla.…”
Section: Introductionmentioning
confidence: 99%
“…Ahuja et al, (2015) showed that the herbicidal potential of clove (Syzygium aromaticum) against four selected weeds (Ageratum conyzoides, Cassia occidentalis, Bidens pilosa and Commelina benghalensis). Goyal (2017) abtracted that the allelopathic impact of essential oil from Melaleuca leucadendra against three selected weeds (Echinochloa crus-galli, Cyperus rotundus and Leptochloa chinensis). Ayeni (2017) stated that the allelopathic potential of leaves from two selected plants (Senna siamea and Pinus carribaea) inhibited of the seed germination and seedling growth in Euphorbia heterophylla.…”
Section: Introductionmentioning
confidence: 99%
“…In light of recent literature, Eos can be used effectively to control weeds [27][28][29][30][31]. Azirak et al (2008) [26] have developed research on the allelopathic effects of Menthax piperita L. and Salvia officinalis L. against various weed species (Amaranthus retroflexus L., Centaurea salsotitialis L., Raphanus raphanistrum L., Sinapis arvensis L., Sonchus oleraceus L. and others).…”
Section: Introductionmentioning
confidence: 99%